Consensus, Institutions, and Supply Response : The Political Economy of Agricultural Reforms in Sub-Saharan Africa - Aksoy, Ataman; Onal, Anil (2012)
During the late 1980s and the 1990s, most countries in Sub-Saharan Africa implemented agricultural policy reforms, along with national political and economic reforms. The agricultural reforms focused on opening up processing and marketing activities to increased competition and eliminating export taxes and restrictions to improve producer incentives. In eight of nine country/commodity case studies analyzed in this paper, output responded positively in the short run to the reforms. In many cases, however, the initial supply response was not sustained in the face of subsequent shocks. The studies suggest that stakeholder consensus on the distribution of sector-specific rents is a key variable affecting the sustainability of supply responses. Agricultural sector reforms lead to large changes in income distribution. The greater the acceptance of the distribution of rents following the reforms, the better sectors are able to accommodate subsequent shocks. In cases where the initial consensus on the distribution of rents is weak, shocks lead to reform reversals in some cases or an inability to design necessary support institutions in others. The diversity in outcomes across similar products and countries suggests it is possible to achieve sector and local level results that differ from national ones.